A real time monitoring system with oral feeding for premature infants - G, Umashankar; Janney, Bethanney; Divakaran, Sindu; G, Meera; Datta, Rima; T, Soundarya (International Journal of Engineering and Technology, 2018)
With the advancement of the medical industry the death rates of the premature newborn infants have been brought under control. Even after the advancements in technology, there is a need for instrument health care interactions due to varied reasons. This aproach discusses about the development of wireless transmission of oral feeding disorder with the help of flow sensor, sound sensor and EMG sensor for the early intervention of the any oral feeding difficulties in the child. The flow sensor is used for sucking and sound sensor is used to detect the swallowing sound and EMG sensor is used to record the muscular activities of the premature infants. And then, the temperature sensor, BP sensor and heart beat sensor will display the values of the premature infants through LCD. In sensing unit, ARM7 (LPC2148) microcontroller is used to program and work the circuit. In software requirements, Keil compiler and embedded C language is used. Zigbee is used for wireless communication and this will act as a transceiver and the final values will be displayed by lab VIEW software through PC. So Finally, This system has designed for a real time monitoring system with oral feeding for the preterm infants.Â Â